Makna Simbol Rangda Sebagai Bentuk Kedigdayaan Perempuan Bali - Arya Pageh Wibawa; I Gede Agus Indram Bayu Artha; I Made Hendra Mahajaya Pramayasa (LP2M ISBI Bandung, 2026)
This study examines the symbolism of Rangda in Balinese culture, focusing on the representation of female power reflected in texts and visual cultural expressions. Rangda, often depicted as an evil figure in Calonarang performances, reflects the duality of transformative feminine power, encompassing both destructive and protective aspects. As a manifestation of the Goddess Durga, Rangda represents feminine energy maintaining the balance of the universe, creating harmony between good and evil through the concept of Rwa Bhineda. This study employs a qualitative, descriptive-analytical approach to explore the symbolic meaning of Rangda across mythological and contemporary contexts. The results show that Rangda is not merely a symbol of evil power but a sacred entity that plays a vital role in maintaining Bali’s cosmic order. The representation of Rangda in visual art and religious rituals enriches the understanding of the role of femininity in maintaining the social and spiritual balance of Balinese society.